Voltage-gated calcium channel subunit α2δ-1 in spinal dorsal horn neurons contributes to aberrant excitatory synaptic transmission and mechanical hypersensitivity after peripheral nerve injury - Koga, Keisuke; Kobayashi, Kenta; Tsuda, Makoto; Kubota, Kazufumi; Kitano, Yutaka; Furue, Hidemasa (Frontiers in Molecular Neuroscience, 2023)
Neuropathic pain, an intractable pain symptom that occurs after nerve damage, is caused by the aberrant excitability of spinal dorsal horn (SDH) neurons. Gabapentinoids, the most commonly used drugs for neuropathic pain, inhibit spinal calcium-mediated neurotransmitter release by binding to α2δ-1, a subunit of voltage-gated calcium channels, and alleviate neuropathic pain. However, the exact contribution of α2δ-1 expressed in SDH neurons to the altered synaptic transmission and mechanical hypersensitivity following nerve injury is not fully understood. In this study, we investigated which types of SDH neurons express α2δ-1 and how α2δ-1 in SDH neurons contributes to the mechanical hypersensitivity and altered spinal synaptic transmission after nerve injury. Using in situ hybridization technique, we found that Cacna2d1, mRNA coding α2δ-1, was mainly colocalized with Slc17a6, an excitatory neuronal marker, but not with Slc32a1, an inhibitory neuronal marker in SDH. To investigate the role of α2δ-1 in SDH neurons, we used clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 system and showed that SDH neuron-specific ablation of Cacna2d1 alleviated mechanical hypersensitivity following nerve injury. We further found that excitatory post-synaptic responses evoked by electrical stimulation applied to SDH were significantly enhanced after nerve injury, and that these enhanced responses were significantly decreased by application of mirogabalin, a potent α2δ-1 inhibitor, and by SDH neuron-specific ablation of Cacna2d1. These results suggest that α2δ-1 expressed in SDH excitatory neurons facilitates spinal nociceptive synaptic transmission and contributes to the development of mechanical hypersensitivity after nerve injury.